Inovasi Akad Musyarakah dalam Perbankan Syariah: Perspektif Hadits dan Relevansinya dengan Praktik Modern - M. Rafly Febryansyah; Khairiyah Fikri Azzahra; Akmalul Hajja; Rukaini Rukaini; Husni Kamal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the innovation of musyarakah contracts in Islamic Banking, Hadith Perspective and its Relevance to Modern Practices. This study uses a descriptive qualitative method through a literature study method, with secondary data in the form of the Qur'an, hadith, and related literature. The analysis was carried out using the syarah maudhui (thematic) method of relevant hadiths. The research findings show that musyarakah values such as justice, transparency, trust (amanah), and the prohibition of betrayal and usury are the ethical and spiritual basis for Islamic banking operations. The application of the musyarakah concept today, including in the form of schemes such as musyarakah mutanaqisah and working capital financing, has encouraged innovation and flexibility in Islamic financial products.